2014
DOI: 10.1088/0004-6256/149/1/26
|View full text |Cite
|
Sign up to set email alerts
|

THE MULTIPLICITY OF MASSIVE STARS: A HIGH ANGULAR RESOLUTION SURVEY WITH THEHSTFINE GUIDANCE SENSOR

Abstract: We present the results of an all-sky survey made with the Fine Guidance Sensor on Hubble Space Telescope to search for angularly resolved binary systems among the massive stars. The sample of 224 stars is comprised mainly of Galactic

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
100
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(109 citation statements)
references
References 71 publications
7
100
2
Order By: Relevance
“…For instance, the primary of HD 93146 A is the earliest star in our sample and has a long period of 1131.4 d. Both this star and HD 123056, another star that probably has a period of 1314 d, might be suitable targets for interferometry. HD 123056 was already observed by Aldoretta et al (2015), but not separated; higher resolution than 10 mas is probably needed. Also in the case of HD 93146 A, high resolution is necessary; at a distance of ≈ 3.0 kpc its semi-major axis might be of the order of 2.5 mas.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the primary of HD 93146 A is the earliest star in our sample and has a long period of 1131.4 d. Both this star and HD 123056, another star that probably has a period of 1314 d, might be suitable targets for interferometry. HD 123056 was already observed by Aldoretta et al (2015), but not separated; higher resolution than 10 mas is probably needed. Also in the case of HD 93146 A, high resolution is necessary; at a distance of ≈ 3.0 kpc its semi-major axis might be of the order of 2.5 mas.…”
Section: Discussionmentioning
confidence: 99%
“…Since the 9 Sgr system is only partially resolved with the FGS, there is an ambiguity between the separation ρ and the optical brightness ratio F 1 /F 2 , and a four-fold ambiguity on the position angle θ. Aldoretta et al (2015) reported ρ min = (18.5 ± 1.9) mas assuming a brightness ratio of unity. Assuming F 1 /F 2 = 1.5 (Paper II, Sana et al 2014), Eq.…”
Section: New Orbital Solutionmentioning
confidence: 99%
“…They found ρ = (4.95 ± 1.05) mas, θ = (242.22 ± 19.95) • and ∆m H = 0.45 ± 0.05 (or F 1 /F 2 = 1.51 ± 0.07, in excellent agreement with our determination of the optical brightness ratio F 1 /F 2 in the range 1.0−1.5 in Paper II). Aldoretta et al (2015) reported an observation taken on 2008.1920 (φ = 0.397) with the Fine Guidance Sensor (FGS) onboard the HST. Since the 9 Sgr system is only partially resolved with the FGS, there is an ambiguity between the separation ρ and the optical brightness ratio F 1 /F 2 , and a four-fold ambiguity on the position angle θ.…”
Section: New Orbital Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Tokovinin et al (2010) obtained Speckle interferometry images of HD 64315 (see Figure 12 in the mentioned study) suggesting that the system may consist of three visual components in a linear configuration (Tokovinin et al 2010). The fit of the x-axis scan with two components is marginal, but experiments with three component made little or no improvement (Aldoretta et al 2015). Therefore the two visual components resolved represent two systems of comparable (but not equal) brightness that are either in a very wide orbit or are not bound.…”
Section: Interferometry and Parallaxmentioning
confidence: 89%